2022
DOI: 10.3390/en15197279
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weather-Forecast-Based Regulation on Energy Savings for Heating in Multi-Family Buildings

Abstract: In this study, based on 19 years of research, an analysis of thermal energy consumption for heating was carried out on a group of 22 residential multi-family buildings located in a temperate continental climate. The buildings were constructed with two different technologies based on prefabricated elements, and most of them were equipped with central heating cost allocators. A predictive control system for the central heating system was installed in the analyzed buildings, followed by a deep thermo-modernizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Burns [29] indicates that the use of various types of window accessories, such as cellular shades, blinds, storm covers, etc., brings energy savings of 10% or more. From the economic point of view, it is also advantageous to support the heating system with an appropriate control system or the use of heat pumps [47,48]. Table 7 offers data on the payback period of the investment, which includes replacing double-glazed PVC windows with triple-glazed PVC windows and wooden doubleglazed windows with aluminum windows.…”
Section: Resultsmentioning
confidence: 99%
“…Burns [29] indicates that the use of various types of window accessories, such as cellular shades, blinds, storm covers, etc., brings energy savings of 10% or more. From the economic point of view, it is also advantageous to support the heating system with an appropriate control system or the use of heat pumps [47,48]. Table 7 offers data on the payback period of the investment, which includes replacing double-glazed PVC windows with triple-glazed PVC windows and wooden doubleglazed windows with aluminum windows.…”
Section: Resultsmentioning
confidence: 99%
“…The application of a weather forecast-based control system allowed the achievement of an additional savings from 4.8% to 23.5%, except for one building, where arise of 2.1% was noticed. In [35], the authors expanded the studied group by another 22 objects. Once again they presented savings obtained using weather forecast control of heating systems, but they did not show relationships for estimation of annual heating demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was concluded that MPC was especially favorable in climates with a high daily amplitude of outdoor temperature, many hours of solar radiation, and long periods of transition between fall and winter as well as between winter and spring. Also, Pietrowska-Woroniak et al [29] reported energy savings when installing weather forecast-based heating control in Polish buildings. Twenty-two residential multi-family buildings built between 1983 and 1996 were included in this study.…”
Section: Introductionmentioning
confidence: 99%